A simple and inexpensive protocol for DNA isolation from avian blood - Kulkarni, Mandar Dilip; Shringarpure, Rohan; Bhatt, Purvi; Prakash, Nikita; Prakash, Vibhu (Journal of the Bombay Natural History Society (JBNHS), 2015)
One of the many challenges encountered during species conservation programmes is genetic management of threatened populations. Declining populations face the threat of genetic drift and/or imbalance in sex ratios, adding to the risk of extinction. The primary step in genetic management of any population is the isolation of DNA from an available tissue sample. Good quality and quantity of DNA, whenever isolated, could be preserved and applied in a number of studies. Collection of blood, which is a very good source of DNA, from birds is possible in conservation programmes. A simple and inexpensive protocol for DNA isolation facilitates processing the blood samples in the field with ease. Commercial kits, though available, are expensive and have limited shelf life. Herein, we report a simple protocol of DNA isolation from avian blood. The protocol did not employ any proteases or organic solvent, making it comparatively inexpensive. This protocol, initially developed for vulture blood, was successfully applied later for other species. The protocol could isolate DNA sufficient for at least 50 amplification reactions. The isolated DNA was found suitable for spectrometry as well as downstream applications like PCR and cloning.